Practice and especially the mandatory agricultural insurance in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
The article describes one of the most important elements of the social functions of the state – agricultural insurance. The author explores the practice and especially agricultural insurance mandatory in modern Kazakhstan. Detailed economic analysis of the problems and prospects of development of agriculture in Kazakhstan based on a Message of the President of the Republic of Kazakhstan «Socio-economic modernization – main direction of development of Kazakhstan» dated 27 January 2012, data from the Ministry of Agriculture and other official sources of information. The basic idea, voiced in the article – the imperfection of the organization areas of agriculture, as the most important sectors of the economy. Agriculture – it is the exclusive sector of the economy, which has been, is and will be the main activity of the person, regardless of the rapid development of urbanization, industry or innovative technologies. In general, there is objective evidence that the agricultural sector in Kazakhstan is a harbinger of economic growth.Key words: agriculture, insurance, agricultural production, agricultural insurance, agriculture, compulsory insurance, agri-food market, agriculture, food products.